2019
DOI: 10.3847/2041-8213/ab4a16
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Drainage in the Protolunar Disk as the Cause for the Depletion in Volatile Elements of the Moon

Abstract: Lunar rocks are severely depleted in moderately volatile elements such as Rb, K, and Zn relative to Earth. Identifying the cause of this depletion is important for understanding how the Earth-Moon system evolved in the aftermath of the Moonforming giant impact. We measured the Rb isotopic compositions of lunar and terrestrial rocks to understand why moderately volatile elements are depleted in the Moon. Combining our new measurements with previous data reveals that the Moon has an 87 Rb/ 85 Rb ratio higher tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 57 publications
9
98
0
Order By: Relevance
“…As inferred for other volatile elements including Zn, Ga, K, and Rb (Day and Moynier, 2014; Day et al., 2020; Kato et al., 2017; Nie et al., 2019; Paniello et al., 2012; Wang and Jacobsen, 2016), we consider it more likely that the heavy Cu isotopic composition of the lunar mantle instead represents (an) episode of extensive volatile loss, consistent with the recent model of lunar volatile element depletions of Nie et al. (2019).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As inferred for other volatile elements including Zn, Ga, K, and Rb (Day and Moynier, 2014; Day et al., 2020; Kato et al., 2017; Nie et al., 2019; Paniello et al., 2012; Wang and Jacobsen, 2016), we consider it more likely that the heavy Cu isotopic composition of the lunar mantle instead represents (an) episode of extensive volatile loss, consistent with the recent model of lunar volatile element depletions of Nie et al. (2019).…”
Section: Discussionsupporting
confidence: 80%
“…Variable degrees of cumulate assimilation or cumulate source incorporation to KREEP basalts therefore do not affect the observation that measured Cu contents of KREEP are much higher than the Cu content predicted for sulfide liquid-saturated urKREEP liquid. Due to the similarity in calculated D i (Figure 7) is consistent with loss of Cd during the Moon-forming event, as proposed for other similarly volatile elements (e.g., Day and Moynier, 2014;Nie et al, 2019).…”
Section: Effect Of Sulfide Liquids On Evolution Of Trace Element Abunsupporting
confidence: 82%
See 1 more Smart Citation
“…Further insight on the mechanism of MVE depletion of the Moon relative to Earth is provided by isotopic studies. It has been found that lunar samples exhibit massdependent isotopic fractionation relative to Earth for various MVEs (K, Rb, Zn, Cl, Sn, Cr, Ga; Herzog et al, 2009;Sharp et al, 2010;Paniello et al, 2012;Boyce et al, 2015Boyce et al, , 2018Kato et al, 2015;Wang and Jacobsen, 2016;Day et al, 2017;Kato and Moynier, 2017;Pringle and Moynier, 2017;Dhaliwal et al, 2018;Sossi et al, 2018;Wang et al, 2019a,b;Stephant et al, 2019;Nie and Dauphas, 2019;Wimpenny et al, 2019, see Figure 4). Different elements show different directions and magnitudes of fractionation and there is considerable variability in the fractionation of different lunar samples for some elements.…”
Section: Moderately Volatile Element Isotopic Fractionationmentioning
confidence: 99%
“…Notably it has become clear that volatile depletion took place under conditions rather distinct from vacuum evaporation. Similarly, volatile element isotope signatures have provided new insights into the conditions of lunar formation (e.g., ref 48,49 ) or into the volatile loss during the existence of magma oceans [14][15][16] . These studies have highlighted that the gas speciation can be inferred from the pattern of isotope fractionation and the degree of fractionation can be intrinsically linked to the rate of transport away from an evaporating surface.…”
Section: Introductionmentioning
confidence: 99%